Pengukuran Arah Kiblat di Dusun Angus Tanjung RT 10/RW05, Desa Tanjung Bugis, Kecamatan Sambas, Kabupaten Sambas - Ramadini, Tan Dwi Rizki; Akbar, Reza (Belalek, 2025)
Determining the Qibla direction is a crucial aspect in the performance of prayer (salat) for Muslims. This study was conducted to determine the Qibla direction at a house located in Dusun Angus Tanjung RT 10/RW 05, Tanjung Bugis Village, Sambas District, Sambas Regency, West Kalimantan. The purpose of this study is to evaluate the accuracy of the Qibla direction using a scientific method involving simple tools through direct observation and manual calculations based on astronomical data. The method applied includes calculating the Qibla direction using specific formulas, supported by a compass and Android-based digital devices to determine the Qibla angle from the house’s geographical coordinates. The measurement results showed that the Qibla direction aligns with the orientation of the house, with no noticeable deviation. This research is expected to provide practical understanding to the community, especially in rural areas, on how to accurately determine the Qibla direction so that prayer can be performed correctly while facing the Kaaba.